The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.1002/ese3.1178
|View full text |Cite
|
Sign up to set email alerts
|

A novel long term solar photovoltaic power forecasting approach using LSTM with Nadam optimizer: A case study of India

Abstract: Solar photovoltaic (PV) power is emerging as one of the most viable renewable energy sources. The recent enhancements in the integration of renewable energy sources into the power grid create a dire need for reliable solar power forecasting techniques. In this paper, a new long-term solar PV power forecasting approach using long short-term memory (LSTM) model with Nadam optimizer is presented. The LSTM model performs better with the time-series data as it persists information of more time steps. The experiment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
29
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(37 citation statements)
references
References 48 publications
0
29
0
Order By: Relevance
“…From the result it is revealed that the COF of GFRPA66 with 35 wt.% is low as compared with GFRPA66 with 30 wt.% reinforcements, since it has better transfer layer formation, increased adhesion of PA66, and low abrasion by glass fiber with less temperature between the contact surfaces. Also the elastic modulus and ultimate strength of glass fiber improve as the weight of glass fiber increases [ 70 , 71 , 72 , 73 ].…”
Section: Resultsmentioning
confidence: 99%
“…From the result it is revealed that the COF of GFRPA66 with 35 wt.% is low as compared with GFRPA66 with 30 wt.% reinforcements, since it has better transfer layer formation, increased adhesion of PA66, and low abrasion by glass fiber with less temperature between the contact surfaces. Also the elastic modulus and ultimate strength of glass fiber improve as the weight of glass fiber increases [ 70 , 71 , 72 , 73 ].…”
Section: Resultsmentioning
confidence: 99%
“…This could result from fuel evaporation during the ignition delay interval, which reduces the temperature . During the premixed combustion stage, uncoated engines for both fuels yield a lower rate of heat generation than coated engines. , This is because a longer ignition delay permits the injection of more fuel. This is attributed to lower HRR achieved for uncoated engines .…”
Section: Resultsmentioning
confidence: 99%
“…Since GP and SVM-Schotastic model performed the best among the other models for FS and CS for this dataset, sensitivity analysis was carried out on it by changing the input combination and taking out one input parameter at a time, as shown in Table 9 and Table 10 . Statistical assessment metrics such as CC, MAE, and RMSE were used to assess each model’s performance [ 72 , 73 , 74 , 75 , 76 , 77 , 78 , 79 , 80 , 81 , 82 ]. Table 9 and Table 10 , demonstrates that the number of curing days followed by CA, C, w and MP is critical in predicting the flexural and compressive strength of a concrete mix.…”
Section: Sensitivity Analysismentioning
confidence: 99%
“…Table 9 and Table 10 , demonstrates that the number of curing days followed by CA, C, w and MP is critical in predicting the flexural and compressive strength of a concrete mix. Due to the pozzolanic reactions, concrete recovers 60% of its strength after 7 days of curing and increases by 99% after 28 days, resulting in a low CC value after removing the aforementioned characteristic [ 76 , 77 , 78 , 79 ]. The pozzolanic reaction is a slow process, and as the curing period lengthens, the amount of gel produced in the mix increases, resulting in greater strength [ 65 ].…”
Section: Sensitivity Analysismentioning
confidence: 99%